Relation between Headache and Mastication Muscle Tone in Adolescents - Ewa Wozniak; Jolanta E. Loster; Aneta Wieczorek (Pain Research and Management)
Headache is a common problem in the population, which decreases the quality of life and makes everyday functioning difficult. It often coexists with typical symptoms of temporomandibular disorders. The objective of the study was to clarify whether there is a relationship between the presence of headache in young volunteers and the mastication muscle tone. Material and Method. Volunteers aged 18 years who underwent general dental examination, clinical evaluation, and examination using the dual-axis diagnostic system Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) form in the Polish language version participated in the study. On the basis of the examination results, these individuals were divided into three groups according to RDC results. A group of healthy individuals (axis I value 0), a group of sick individuals (axis I diagnosis Ia, IIa, or IIIa), and a group of individuals suffering from depression (axis II values 1–3) were singled out. Then, volunteers were divided into two groups: group I reporting headache and group II without any pain. In each of these individuals, the contractile activity of the masseter muscles and anterior temporal muscles was recorded bilaterally as the surface electromyographic activity (sEMG) at rest, during swallowing, and maximum clenching. The activity index ranging between +100 (activity of the masseter muscles only) and −100 (activity of the anterior temporal muscles only) was used to indicate the predominance of activity of the study muscles. Results. The statistical analysis of data showed that there was a significant relationship between the presence of headache and a change in the mastication muscle tone, expressed as the predominant activity of the temporal muscles, only in the group of sick individuals during maximum clenching. Summary. The diversity of sEMG results implies that a change in the mastication muscle tone is not a direct consequence of headache, but it has to be modified by other factors.